Pemberdayaan Perempuan Melalui Pelatihan Keterampilan dan Literasi Keuangan - Hasbiyadi Hasbiyadi; Abd. Mansyur; Zulfkri Soekarno; Ansir Launtu; Lucina Kanji; Mursida Abu; Ahmad Anto (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Women's empowerment at the village level is a strategic step in strengthening household economics, especially in transitional areas such as Sunggu Manai Village, Pattallassang District. The main problems faced by partners are low productive skills and a lack of financial literacy, leading to economic dependence and vulnerability to illegal lending schemes. This community service activity aims to increase women's economic capacity through technical skills training and financial management. The method used is Asset-Based Community Development (ABCD) with stages of socialization, hardskill training (making processed products), and financial literacy workshops (cash management and investment awareness education). The results of the activity showed an increase in participants' knowledge by 45% based on pre-test and post-test scores. Furthermore, participants were able to manufacture products with marketable packaging standards and gained a new understanding regarding the separation of business cash from domestic cash. The conclusion of this activity is that the integration of practical skills and financial intelligence can encourage women's economic independence and create more sustainable family financial resilience.